Alleviating insomnia should decrease the risk of irritable bowel syndrome: Evidence from Mendelian randomization - Bao, Wenzhao; Qi, Li; Bao, Yin; Wang, Sai; Li, Wei (Frontiers in Pharmacology, 2022)
Background: Associations have been reported between sleep and irritable bowel syndrome (IBS), however, whether there exists causation between them is still unknown. Methods: We employed the Mendelian randomization (MR) design to explore the causal relationship between sleep and IBS. All genetic associations with sleep-related traits reached genome-wide significance (p-value < 5x10-8). The genetic associations with IBS were obtained from two independent large genome-wide association studies (GWAS) where non-FinnGen GWAS was in the discovery stage and FinnGen GWAS in the validation stage. Primarily, the inverse-variance weighted method was employed to estimate the causal effects and a meta-analysis was performed to combine the MR estimates. Results: In the discovery, we observed that genetic liability to the “morning” chronotype could lower the risk of IBS (OR = 0.81[0.76, 0.86]). Also, the genetic liability to insomnia can increment the risk of IBS (OR = 2.86[1.94, 4.23]) and such causation was supported by short sleep duration. In the validation stage, only insomnia displayed statistical significance (OR = 2.22[1.09, 4.51]). The meta-analysis suggested two genetically-determined sleep exposures can increase the risk of IBS, including insomnia (OR = 2.70[1.92, 3.80]) and short sleep duration (OR = 2.46[1.25, 4.86]). Furthermore, the multivariable MR analysis suggested insomnia is an independent risk factor of IBS after adjusting for chronotype (OR = 2.32[1.57, 3.43]) and short sleep duration (OR = 1.45[1.13, 1.85]). The IBS cannot increase the risk of insomnia in the reverse MR analysis. Conclusion: Genetic susceptibility to insomnia can increase the risk of IBS and improving sleep quality, especially targeting insomnia, can help to prevent IBS.